2013
DOI: 10.5588/pha.13.0028
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of HIV-infected women with tuberculosis in Dar es Salaam, Tanzania

Abstract: HIV-positive women with TB have substantial 24-h deficits in energy and protein intake, report significant food insecurity and gain minimal weight on anti-tuberculosis treatment. Enhanced dietary education together with daily supplementation of 1000 kcal with 40 g protein may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Reporting of food insecurity was inconsistent across the included articles. Besides the well-validated HFIAS [14,41,46,56,57], authors evaluated food insecurity by diagnosing malnutrition using BMI values [14,47,49,50,[52][53][54]58], mid-upper arm circumference (MUAC) [47][48][49], weight-for-height z-score [48], lean mass index (LMI) [51,52], fat mass index (FMI) [51,52], bioelectrical impedance analyzer (BIA) measurements [51,52], food energy/nutritional intake of macronutrients [43,45,51,54], dietary diversity score [53], weight gain or loss [14,41,51,53,57], clinical symptoms such as kwashiorkor, pellagra, and marasmus [43,45], qualitative reports of food availability [42,55], food sufficiency [42], or presence/absence of nutritional support [43,44,50]. A couple of the studies only reported a narrative description of food insecurity, without stating the measure used [42,44,…”
Section: Evidence Of Food Insecurity In Individuals With Hiv/aids and Tb Co-infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reporting of food insecurity was inconsistent across the included articles. Besides the well-validated HFIAS [14,41,46,56,57], authors evaluated food insecurity by diagnosing malnutrition using BMI values [14,47,49,50,[52][53][54]58], mid-upper arm circumference (MUAC) [47][48][49], weight-for-height z-score [48], lean mass index (LMI) [51,52], fat mass index (FMI) [51,52], bioelectrical impedance analyzer (BIA) measurements [51,52], food energy/nutritional intake of macronutrients [43,45,51,54], dietary diversity score [53], weight gain or loss [14,41,51,53,57], clinical symptoms such as kwashiorkor, pellagra, and marasmus [43,45], qualitative reports of food availability [42,55], food sufficiency [42], or presence/absence of nutritional support [43,44,50]. A couple of the studies only reported a narrative description of food insecurity, without stating the measure used [42,44,…”
Section: Evidence Of Food Insecurity In Individuals With Hiv/aids and Tb Co-infectionmentioning
confidence: 99%
“…Among studies that used the Household Food Insecurity and Access Scale (HFIAS) to assess food insecurity (n = 5), all reported the presence of food insecurity [14,41,46,47,57] but only one study reported the actual HFIAS score, where the average score was 6 (range: 1-14) [41]. Another study at baseline started with 92% food insecurity at enrollment, which declined to 73% food insecurity, after the nutritional support and TB treatment initiative was administered for 6 months [14].…”
Section: Wang Et Al (2020) [57]mentioning
confidence: 99%
See 3 more Smart Citations